2018
DOI: 10.1111/jnc.14593
|View full text |Cite
|
Sign up to set email alerts
|

Increased tau phosphorylation follows impeded dopamine clearance in a P301L and novel P301L/COMT‐deleted (DM) tau mouse model

Abstract: In Alzheimer’s disease, the phosphorylation of tau is a critical event preceding the formation of neurofibrillary tangles. Previous work exploring the impact of a dopamine blocking antipsychotic on tau phosphorylation in a tau transgenic model suggested that extracellular dopamine may play a regulatory role in the phosphorylation state of tau. In order to test this hypothesis, and in order to develop a mouse model of impaired dopamine metabolism and tauopathy, an extant P301L transgenic tau model of Alzheimer’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…Tau pathology has also been suggested to be facilitated by alterations to the LC-NA system as demonstrated in rodents (7). Moreover, whilst no significant relationship between NA/MHPG and tau was observed in our analyses, MHPG more than NA may be related to p-tau as animal studies have shown that NA Omethylation in MHPG is necessary for tau spreading (78).…”
Section: More Studies Are Required To Determine the Relationship Between Brain Pathology And Csf Na/mhpg Biomarkerscontrasting
confidence: 43%
“…Tau pathology has also been suggested to be facilitated by alterations to the LC-NA system as demonstrated in rodents (7). Moreover, whilst no significant relationship between NA/MHPG and tau was observed in our analyses, MHPG more than NA may be related to p-tau as animal studies have shown that NA Omethylation in MHPG is necessary for tau spreading (78).…”
Section: More Studies Are Required To Determine the Relationship Between Brain Pathology And Csf Na/mhpg Biomarkerscontrasting
confidence: 43%
“…Recently, the novel P301L(+/+)/ COMT(−/−) (DM) mouse, fashioned as a hyperdopaminergic tau mouse model of psychotic AD, was observed to have an increased frontal dopamine surge in response to catecholamine reuptake inhibition relative to COMT competent P301L mice. Moreover, the increase in dopamine was associated with an increase in tau phosphorylation, recapitulating an established pathologic correlate of psychosis in AD (104). Another recent effort looked to model the synaptic pathology of psychosis in AD.…”
Section: Examples Of Novel Animal Models Of Psychosis In Admentioning
confidence: 89%
“…Interestingly, a SNP associated with increased DAT1 expression [30] is predictive of higher brain atrophy and associated with increased dementia [31]. Though recent data suggest that dopamine surges in the extracellular space increase ptau [32], the physiological relevance of tau‐induced increased levels of DAT1 in the context of AD‐type amyloidosis will need further study. Loss in Trem2 function underlies neurodegenerative pathology in AD and is associated with a specific microglial phenotype associated with neuritic changes in amyloid models [20].…”
Section: Discussionmentioning
confidence: 99%